Meanings of therapeutic recreation: professionals' perspectives. Issue 1 (2nd January 2021) - Genoe, M. Rebecca; Cripps, Douglas; Park, Kathy; Nelson, Sherri; Ostryzniuk, Linda; Boser, Donna
ABSTRACT: Debate regarding definitions and philosophies of therapeutic recreation (TR) is ongoing. Those who favour the recreational therapy approach view leisure as a modality to improved health, whereas those who ascribe to the therapeutic recreation approach prioritize leisure experiences over addressing symptoms of illness or disability. However, there is a paucity of research exploring professionals' perspectives on the meaning of TR. To address this gap, we conducted 19 interviews and 8 focus groups with TR professionals. Thematic analysis was used to generate several themes related to meanings of TR. These meanings included enabling joyful and meaningful experiences, enhancing well-being and quality of life, enabling choice and independence, relationship-building and belonging, and personal and professional rewards . Our findings demonstrate that participants tended towards a leisure-focused, strengths-based approach to TR by valuing their clients' leisure preferences and choices while focusing on their abilities rather than deficits.